Visualization of cracks by using the local Voronoi decompositions and distributed software. (June 2015) - Pacevič, Ruslan; Kačeniauskas, Arnas; Markauskas, Darius
Highlights: Local Voronoi decompositions are applied to extraction of crack surfaces. Cracks propagate in mono-dispersed particulate media simulated by the DEM. The geometry of crack surfaces is accurately defined by faces of the decomposition. Generation of local decompositions rather than global meshes reduces execution time. The sufficiently high speed-up of distributed visualization software is achieved. Abstract: The paper presents a novel visualization technique for cracks propagating in mono-dispersed particulate material. The proposed technique is based on local space decompositions generated in fractured areas. The contact surfaces of the neighboring particles are defined by the local Voronoi decomposition generated according to the lattice topology employed in computations of the discrete element method. The visual model validation helps to indicate the regions of a highly deformed lattice, where the defects detected between the pairs of the neighboring particles on the lattice connections cannot be directly mapped onto the relevant edges of the Voronoi diagram. The parallel implementation of the visualization technique is based on the domain decomposition and two layers of ghost vertices and connections. The technique is implemented in the distributed visualization software VisPartDEM. Datasets of the elastic solid problem exhibiting non-uniform distribution of fracture force values are considered to validate the performance of the proposed technique. The parallel speed-up of the visualization software is investigated. The superior performance of the applied local technique is compared to the performance observed by using the standard global Voronoi algorithm.